Exploration of the meaning of connectedness for older people in long‐term care in context of their quality of life: a review and commentary. (25th February 2013) - Cooney, Adeline; Dowling, Maura; Gannon, Mary E.; Dempsey, Laura; Murphy, Kathy
<x xml:space="preserve">Abstract</x> Background A link between 'quality of life' and 'connectedness' is emerging in the literature. However, there has been little debate on what 'connectedness' means and how it can be fostered in long‐term care settings. This review examines the meaning of 'connectedness' in long‐term care. Aim This paper critically examines the meaning of 'connectedness' in the context of its contribution to the quality of life of older people living in long‐term care settings. Method Key databases (CINAHL, PsychInfo and Medline) were searched systematically. Fourteen papers and two book chapters met the inclusion criterion of papers exploring 'connectedness for older people in residential care'. Conclusions The experience of connectedness for older people in long‐term care settings is linked with quality of life and successful ageing. Fundamental prerequisites of connectedness for older people are: self‐awareness, meaningful relationships with family and friends, involvement in meaningful activities and connections with wider society. However, barriers to these prerequisites are evident for many residents in long‐term care settings. Implications for practice Register and Herman (Advances in Nursing Science, 33, 2010, 53) identify six connections that combine to generate connectedness for older people. These connections are representative of the factors associated with increased quality of life for residents living in long‐term care settings. The six connections are helpful in identifying areas to focus on when planning person‐centred care.